The Use of Mobile-Based Self Learning to Enrich Children’s English Vocabularies - Imaratul Ulwiyah (Departement of Mathematics Education, 2023)
The aim of this study was to examine self-learning using mobile-based to help children enrich their English vocabularies. This learning process used an apps called ‘English for Children’ (Bahasa Inggris Untuk Anak). It consists of twenty (20) vocabulary categories. They are Alphabet, Numbers, Colors, Shapes, Family, Body parts, Days of the week, Months of the year, Fruits, Vegetables, Animals, Birds, Food, Clothes, Kitchen, Bathroom, Living room, School, Sports, and Professions. Every word category is followed by four (4) learning sections such as ‘Learn’, ‘Writing’, ‘Find the word’, and ‘Find the picture’. Every section is served with pictures (visualization). Exercises can also be found in the ‘Writing’, ‘Find the word’, and ‘Find the picture’ sections as a benchmark of learning progress. The participants were 10 children age 10-11 years old. This type of learning was using student-centered model. The qualitative research method is used in this research. The systematic analysis of textual data was obtained via interviews, surveys, focus groups and diary entries. The result can be seen through the score of the exercise. Surprisingly, the score has risen significantly. Children could pass the exercise easily with the help of pictures. It means that by applying learning English vocabularies through mobile-based self-learning indicated that there was any significant difference before and after using this method.